New and Improved Safety and Risk Assessment Model for Petrol Fuel Station - Mirza, Munir (2011)
Measurement of risk levels posed by hazardous activities on organizations assets, entities and processes are of highly significance. This can be done with risk assessment process. Risk assessment is the method to evaluate the risk arising from many activities, during the process. Many risk assessment criteria are using in many organizations to calculate the risk. Three (03) risk assessment criteria were selected to determine the risk associated with hazardous activities. 1267 activities were analyzed by using each risk assessment method. It was noticed that hazardous activities ranking in these (03) three criteria were different from one another. Fuel stations data was used for analysis. Risk variations are an indicator that there exists a significant gap among these criteria. By using fuel station data new risk and safety assessment criterion developed. Analysis of activities was carried out. Results obtained highlighted that fatalities and major accidents not only be considered to improve safety records but the reduction of incidents and near misses should be of vital importance. Near miss, accidents, incidents and miscellaneous cases were analyzed. Severity index calculated and then it multiplied with frequency to determine the risk level. Based upon this risk factor management should decide the areas of further improvement. Risk assessment is vitally important for discussion in HSE committee meetings. During analysis it was highly felt that one (01) major cause for occurrences of accidents, incidents, near misses and miscellaneous cases during working is the use of incompatible risk assessment criterion. In this study a new and improved risk and safety and risk assessment model developed and proposed for further implementation.